The Prosopography of the Later Roman Empire - A.H.M. Jones; J. R. Martindale; J. Morris (Cambridge University Press, 1971)
The Prosopography of the Later Roman Empire, by A.H.M. Jones, J. R. Martindale, and J. Morris. This invaluable reference work was begun by Jones and completed by two of his student-colleagues. The volumes, which are bookmarked and searchable, contain names and biographical information about people who lived in the 3rd-7th centuries and had some connection with the Roman Empire, and who also were mentioned in Western and/or Eastern historical sources, documents, inscriptions, and elsewhere. Wikipedia has an entry on the history and impact of this remarkable publication (The Prosopography of the Later Roman Empire). Internet Archive has a selection of works by A.H.M. Jones. Compiled by Robert Bedrosian. Available as a separate pdf file is T. D. Barnes' collection of Additions. Volume 1 A.D. 260-395 (Cambridge, 1971) Volume 2 A.D. 395-527  (1980) Volume 3 A.D. 527-641, in two parts (1992)
Keywords: History